Síndrome de DRESS en el paciente quirúrgico: diagnóstico diferencial, manejo perioperatorio y desafíos terapéuticos - Vanessa Cecilia Iza-Sanga; Juan Felipe Acosta-Orejuela; Nicolás Montes-Salazar; Carlos Steven Bodniza-Freire; Byron Allan Cachott-Brito (Revista Metropolitana de Ciencias Aplicadas, 2026)
Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome is a severe adverse drug reaction that poses a particular challenge in the perioperative setting due to polypharmacy, clinical complexity, and potential overlap with other complications. The objective of this review was to characterize DRESS syndrome in surgical patients, with emphasis on its recognition and therapeutic management. A literature review was conducted, including 25 references published over the last ten years in Spanish, English, and Portuguese. The evidence analyzed indicates that early recognition of the syndrome, identification and immediate withdrawal of the causative drug, and timely initiation of corticosteroid therapy remain the main pillars of treatment. In severe or refractory cases, therapeutic alternatives such as cyclosporine, intravenous immunoglobulin, plasmapheresis, and selected biological agents targeting mechanisms related to T lymphocytes and interleukins have been used. However, evidence supporting these interventions remains limited, and sufficiently standardized protocols are still lacking. In surgical patients, management requires individualized interventions, general supportive care, close monitoring, and timely treatment of acute complications. It is concluded that DRESS is a potentially severe hypersensitivity reaction whose perioperative presentation poses significant diagnostic and therapeutic challenges, particularly because of the risk of multiorgan involvement. Although currently available diagnostic tools and early corticosteroid therapy facilitate clinical management, important knowledge gaps remain, highlighting the need for further research involving larger populations and robust methodologies to establish specific therapeutic strategies for the perioperative setting.